The role of Liberation Theology during the armed conflicto in Guatemala and the work of Ricardo Falla, 1960 – 1996 - Barrientos Valverde, Jorge (2022)
The armed conflict in Guatemala is known in the Latin American region as one of the most violent of the 20th century. The violent structures of political and economic domination, based on the deeply racist, classist and misogynistic colonial heritage, generated in that country a series of popular uprisings of the oppressed groups after 1960 in order to build a more equitable, just and supportive society. For this purpose, the role of the Catholic Church was then very controversial, among the most conservative and complacent sectors with the established order and the groups that joined the social protest movements. Following this line, the present work intends to study the role of social Catholicism in Guatemala and the representatives of Liberation Theology such as Ricardo Falla and other colleagues during the civil war, in order to better understand the power struggles, the disputes ideological and social tensions that this nation experienced.